A Tributação das Sociedades Insolventes: Evidência Empírica em Portugal - Dinis, Ana (2016)
This article discusses the issue of taxation of insolvent companies in Portugal, particularly regarding the Portuguese tax on revenue of legal entities (IRC). For this purpose, first, some considerations on the legal framework of insolvent companies are woven and, second, their tax regime is analyzed. Then, a brief review of the main studies that, in the international context, analyze and debate major issues derived from the tax regime of insolvent companies is conducted, particularly in Brazil, Spain, United States, and Italy. Finally, there are the results of an empirical study conducted in Portugal, in 2013, which evaluates and compares the opinions of insolvency administrators (IA), the tax and customs authority (TA), and court magistrates (CM), in order to contribute to a better solution concerning business taxation under this regime. Respondents (IA, TA, CM) demonstrate objective thinking about the fact they believe it is very important that the Portuguese Code of Insolvency and Business Recovery (CIRE) and the Portuguese Code of Tax on Revenue of Legal Entities (CIRC) are modified, now to make clear whether the settlement of property ownership of an insolvent estate is liable to the IRC, then to assign a chapter specifically devoted to the subject of taxation on insolvency in Portugal.